Clinical and epidemiological profile of leprosy in the state of Acre: a retrospective study - Silva, Marina de Souza (2014)
Objective: To describe the epidemiological situation of leprosy in the State of Acre. Method: It is a retrospective, descriptive study carried out in the State of Acre using the Information System Database on Notifiable Diseases with a quantitative approach during the period of 2004-2012. Results: 2 691 cases of leprosy were recorded, 60.6% male, older than 15 years (90.1%), brown (81.2%), incomplete primary education (55.9%), from a rural area (61.4%). 49% of cases were classified as borderline patients, 80.2% were grade of disability zero at diagnosis. In 2011from only 478 out of 2146 registered contacts were evaluated. Conclusion: Despite the predominance of grade of disability zero at the time of diagnosis, the high number of borderline patients and the low percentage of active search for contacts may indicate maintenance of the transmission and high rates of hidden prevalence of leprosy, which refers to operational difficulties faced by the health services to perform early diagnosis.